LEARNER INITIATIVE AND ORAL PROFICIENCY: INVESTIGATING THE LINK IN ENGLISH LANGUAGE INSTRUCTION - Suryanto Suryanto; Muhammad Fakhri; Turki Alsolami; Bolormaa Shinjee (Indonesian EFL Journal, 2025)
In the context of 21st-century globalization and technological progress, English has become a crucial worldwide lingua franca, especially in non-native English-speaking nations such as Indonesia. Although English has been included into the Indonesian education system at all levels, numerous students encounter difficulties in attaining oral fluency despite extensive formal training. This study examines the correlation between learner initiative and students' oral competency in English, specifically targeting learners in the English Language Education Department of a private institution in Yogyakarta. Utilizing a quantitative correlational study methodology, data were gathered from 97 students through a validated questionnaire to evaluate learner initiative and academic records to assess speaking competence. Descriptive analysis revealed a high level of learner initiative (M = 45.20) and good speaking ability (M = 3.35). Spearman’s rho correlation analysis revealed a statistically significant albeit modest positive association (rs = 0.367, p = 0.001) between learner initiative and speaking proficiency. These findings suggest that while initiative is meaningful in oral language development, it is not the sole determinant of speaking proficiency. The study highlights the need for instructional strategies that foster learner autonomy and address other influencing factors such as anxiety, interaction opportunities, and feedback. The findings supplement the expanding literature highlighting the significance of internal learner traits, especially initiative, as crucial determinants of success in EFL speaking performance